Reference Note on Trade in Financial Services. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This note addresses key issues with respect to trade policy in financial services and its linkages to capital flows, and prudential regulations and supervision under the General Agreement on Trade in Services (GATS), preferential trade agreements (PTAs), and bilateral investment treaties (BITs). The note should help inform the advice that country teams provide on such issues in the context of surveillance, program negotiations, and technical assistance. It is a response to the Executive Board's call for guidance in this area stemming from the 2009 IEO Evaluation of IMF Involvement in International Trade Policy Issues.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet